Generation of Human Pluripotent Stem Cell‐Derived Polarized Hepatocytes. Issue 1 (10th January 2022) - Bushweller, Leila; Zhao, Yuanyuan; Zhang, Fan; Wu, Xianfang
Abstract: Human pluripotent stem cell (hPSC)–derived hepatocyte‐like cells (HLCs) are valuable tools to study liver biology. HLCs, however, lack certain key in vivo characteristics relevant to their physiological function. One such characteristic is cellular polarity, which is critical to hepatocyte counter‐current flow systems involving canalicular bile secretion and sinusoidal secretion of large quantities of serum proteins into blood. Model systems using non‐polarized hepatocytes, therefore, cannot recapitulate this physiological function of hepatocytes. Here, we describe a stepwise protocol to generate hPSC‐derived polarized HLCs (pol‐HLCs), which feature clearly defined basolateral and apical membranes separated by tight junctions. Pol‐HLCs not only display many hepatic functions but are also capable of directional cargo secretion, mimicking the counter‐current flow systems. We describe protocols for stem cell culture maintenance and for differentiating hPSCs into pol‐HLCs. In addition, we describe protocols to assay the pol‐HLCs for basic hepatic functions and polarized hepatic characteristics. Once successfully differentiated, these pol‐HLCs can be used as an in vitro model system to study hepatocyte biology, disease mechanisms, genetic variation, and drug metabolism. The establishment of hepatic polarity from non‐polarized hPSCs also provides a useful tool to study the development and maintenance of hepatic polarity. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Maintenance of hPSCs Basic Protocol 2 : Differentiation of hPSCs to pol‐HLCs Basic Protocol 3 : Assaying pol‐HLCs for basic hepatic functions Support Protocol 1 : Assessment of pol‐HLC monolayer tightness Support Protocol 2 : Assessment of pol‐HLC polarity